2017
DOI: 10.1186/s13068-017-0705-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the glucose dual-affinity transport system in Neurospora crassa: pleiotropic roles in nutrient transport, signaling, and carbon catabolite repression

Abstract: BackgroundThe glucose dual-affinity transport system (low- and high-affinity) is a conserved strategy used by microorganisms to cope with natural fluctuations in nutrient availability in the environment. The glucose-sensing and uptake processes are believed to be tightly associated with cellulase expression regulation in cellulolytic fungi. However, both the identities and functions of the major molecular components of this evolutionarily conserved system in filamentous fungi remain elusive. Here, we systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 92 publications
(119 reference statements)
5
100
0
Order By: Relevance
“…Differential phosphorylation of key components in substrate perception was demonstrated for the cellulolytic transcription factors CLR-1, a major cellulase regulator in N. crassa (Coradetti et al, 2012, 2013) and XLR-1 (a cellulase/hemicellulase regulator conserved in fungi (Samal et al, 2017) as well as a cellobionic acid transporter, CBT-1, after exposure to cellulose (Xiong et al, 2014). Carbon catabolite repression (CCR) is another central regulatory mechanism involved in substrate perception and metabolic regulation found in a wide range of microbial organisms that ensures the preferential utilization of glucose over less favorable carbon sources (Aro et al, 2005; Vinuselvi et al, 2012) and therefore affects the fungal response to nutrient availability (Fernandez et al, 2012; Nguyen et al, 2016; Bang Wang et al, 2017). Differential phosphorylation of CCR-related proteins after addition of different carbon sources was previously observed in a proteome analysis of Trichoderma reesei (Nguyen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Differential phosphorylation of key components in substrate perception was demonstrated for the cellulolytic transcription factors CLR-1, a major cellulase regulator in N. crassa (Coradetti et al, 2012, 2013) and XLR-1 (a cellulase/hemicellulase regulator conserved in fungi (Samal et al, 2017) as well as a cellobionic acid transporter, CBT-1, after exposure to cellulose (Xiong et al, 2014). Carbon catabolite repression (CCR) is another central regulatory mechanism involved in substrate perception and metabolic regulation found in a wide range of microbial organisms that ensures the preferential utilization of glucose over less favorable carbon sources (Aro et al, 2005; Vinuselvi et al, 2012) and therefore affects the fungal response to nutrient availability (Fernandez et al, 2012; Nguyen et al, 2016; Bang Wang et al, 2017). Differential phosphorylation of CCR-related proteins after addition of different carbon sources was previously observed in a proteome analysis of Trichoderma reesei (Nguyen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 20 putative hexose (glucose) transporters showed changed expression pattern in Δ Tlstp1 compared to the WT strain (8 upregulated, 12 downregulated). Particularly, the gene SMF2FGGW_104114 encoding a putative hexose transporter that shares high sequence identity (75.9%) with the high‐affinity glucose transporter Hgt‐1 in N. crassa (Wang et al, ) is significantly downregulated during both the 36‐hr and 60‐hr cultivation period. Two relatively close homologs (SMF2FGGW_104773 and SMF2FGGW_101765) of the low‐affinity glucose transporters, Glt‐1 in N. crassa and HxtB in A. nidulans (Dos Reis et al, ; Wang et al, ), also exhibit downregulated expression in the Δ Tlstp1 mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Tlstp1 is located in the membrane, which is consistent with the sequence analyses that Tlstp1 encodes a putative membrane transporter. Further glucose-mediated analyses showed that, in contrast with the yeast cells expressing the glucose transporter hgt-1 (Wang et al, 2017) which showed significant growth, cells expressing Tlstp1 exhibited hardly any growth when glucose was used as the sole carbon source (Figure 2b), suggesting that TlSTP1…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh cells were harvested and RNA was isolated with TRIzol reagent (Invitrogen, Carlsbad, CA, USA). Total RNA extraction was performed as described in a previous study …”
Section: Methodsmentioning
confidence: 99%